2022
DOI: 10.1097/won.0000000000000854
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Face-to-Face Education and Multimedia Software Education on Adjustment of Patients With Intestinal Ostomy

Abstract: PURPOSE: The aim of this study was to compare the effect of face-to-face versus multimedia education on the adjustment of patients to an intestinal ostomy. DESIGN: Randomized clinical trial. SUBJECT AND SETTING: The sample comprised 135 patients with new ostomies randomly assigned to 3 groups (control, face-to-face, and multimedia education). Data were collected from November 2018 to May 2019; the study setting was Rasul-e Akram and Imam Khomeini Hospitals, Tehran, Iran. METHODS: The control group receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…28,33 Three months after discharge, scores on the Ostomy Adjustment Inventory-23 were better for patients who initially viewed a multimedia educational program during hospitalization when compared to the control and traditional education groups in a randomized controlled trial, where intervention patients were regularly contacted via phone after hospitalization and encouraged to apply educational content. 28…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…28,33 Three months after discharge, scores on the Ostomy Adjustment Inventory-23 were better for patients who initially viewed a multimedia educational program during hospitalization when compared to the control and traditional education groups in a randomized controlled trial, where intervention patients were regularly contacted via phone after hospitalization and encouraged to apply educational content. 28…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a prospective study in Sweden suggested that their low prevalence of peristomal skin complications was likely influenced by regular follow-up care for 1 year by a WOC nurse 13. In recent studies, use of technology, where the resource can be taken home and viewed as needed following hospital discharge, has been found to be beneficial for patients undergoing ostomy surgery 28,33. Three months after discharge, scores on the Ostomy Adjustment Inventory-23 were better for patients who initially viewed a multimedia educational program during hospitalization when compared to the control and traditional education groups in a randomized controlled trial, where intervention patients were regularly contacted via phone after hospitalization and encouraged to apply educational content 28…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 A Persian language version of the OAI-23 was evaluated for face and content validity; the test-retest correlation coefficient for this instrument was 0.81. 13,26 Resilience Scale…”
Section: Ostomy Adjustment Inventory-23 (Oai-23)mentioning
confidence: 99%